On a fractional differemtial equation with Jumaries fractional derivative - Ren, Bijun (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
By a counterexample, we prove that the results obtained in [1] are incorrect and there exist some theoretical mistakes in fractional complex transform.